Species Diversity, Turn-over and Resource Apportionment among Various Plant Species in a Western-Himalayan forest - Pande, P. K.; Negi, J. D. S.; Sharma, S. C. (Indian Forester, 2000)
In this paper, species diversity, species turn-over and resource apportionment among the various species at selected sites of Western-Himalayan forest situated at Sandev, Distt. Pithoragarh (U.P.) are described. The whole are is divided into four sub sites as per their aspect, altitude and vegetation. In general, Quercusleucotrichophora, Pieris ovalifolia, Rhododendron arboreum, Alnus nepalensis and Macaranga denticulata dominate the site except site-III, where Pinus rOlCburghii forms its community with P. ovalifolia and R. arboreum. The density value range (plant/100m2) was 6.37-12.37 for tree layer; 21-74 for shrubs and 6182-11400 for herb layer. Total basal cover (cm2/100m2) ranged in between 1986-4612 for tree layer; 17-50 for shrubs and 246-497 for herbaceous layer. Diversity.index is higher for herbs and lowest for trees. Site-IV is more diverse than of the other sites for trees and shrubs while site-II is more diverse than of the other sites as far as herbs are concerned. Site-III and IV are the more similar sites whereas site-I and IV showed least similarity. In general, log and log-normal distribution of species is followed by most of the Bites for all the life.forms, which is indicative of higher interspecific competition among the various species at their respective sites.